The PoGO+ view on Crab off-pulse hard X-ray polarization. (26th February 2018) - Chauvin, M; Florén, H-G; Friis, M; Jackson, M; Kamae, T; Kataoka, J; Kawano, T; Kiss, M; Mikhalev, V; Mizuno, T; Tajima, H; Takahashi, H; et al.
Abstract: The linear polarization fraction (PF) and angle of the hard X-ray emission from the Crab provide unique insight into high-energy radiation mechanisms, complementing the usual imaging, timing, and spectroscopic approaches. Results have recently been presented by two missions operating in partially overlapping energy bands, PoGO+ (18–160 keV) and AstroSat CZTI (100–380 keV). We previously reported PoGO+ results on the polarization parameters integrated across the light curve and for the entire nebula-dominated off-pulse region. We now introduce finer phase binning, in light of the AstroSat CZTI claim that the PF varies across the off-pulse region. Since both missions are operating in a regime where errors on the reconstructed polarization parameters are non-Gaussian, we adopt a Bayesian approach to compare results from each mission. We find no statistically significant variation in off-pulse polarization parameters, neither when considering the mission data separately nor when they are combined. This supports expectations from standard high-energy emission models.